Answer:
See explanation
Step-by-step explanation:
The question has conflicting details
[tex]f(x) = 2x + 5[/tex]
[tex]f(x) = 2x + 5[/tex] and three halves doesn't sound correct.
So, I will take f(x) as
[tex]f(x) = 2x + 5[/tex]
Next, solve for the inverse function
Replace f(x) with y
[tex]y = 2x + 5[/tex]
Swap x and y
[tex]x = 2y + 5[/tex]
Make 2y the subject
[tex]2y = x-5[/tex]
Make y the subject
[tex]y = \frac{x-5}{2}[/tex]
Replace y with the inverse sign
[tex]f^{-1}(x) = \frac{x-5}{2}[/tex]
So, now we can calculate any value from the original function and from the inverse function.
For instance:
[tex]f^{-1}(7) = \frac{7-5}{2} = \frac{2}{2} = 1[/tex]
[tex]f(1) = 2*1 + 5 = 2+5=7[/tex]